Rapid postoperative platelet decline in a lung adenocarcinoma with sarcomatoid differentiation and concomitant JAK2 V617F mutation: a case report - Deng, Luojie; Li, Xiaoping (Frontiers in Oncology, 2025)
BackgroundLung cancer is one of the leading causes of cancer incidence and mortality worldwide. At the molecular level, its development involves aberrations in multiple oncogenic pathways. Here, we report a rare case of lung adenocarcinoma with sarcomatoid differentiation and profound thrombocytosis (1,350 × 109/L), harboring concurrent TP53, JAK2 V617F, and MET exon 14 skipping mutations.Case presentationA 75-year-old female underwent VATS wedge resection for pathological stage IB lung adenocarcinoma. Platelet counts dropped from 1,350 to 572 × 109/L within 3 weeks postoperatively and remained stable during the 6-month follow-up period. No adjuvant therapy was administered. Molecular profiling of the resected tumor revealed concurrent TP53, JAK2, and MET mutations.ConclusionThis case represents a rare coexistence of JAK2 V617F, MET, and TP53 mutations in lung adenocarcinoma. A marked postoperative decline in platelet count was observed without adjuvant therapy, suggesting a possible tumor-associated reactive thrombocytosis rather than a primary hematologic disorder. Recognition of such platelet dynamics may aid in the clinical assessment and follow-up of lung cancer patients.